Design of Flettner Rotor in Container Carrier 4000 DWT with CFD - Arief, Irfan Syarif; Santoso, Agoes; Azzam, Abdullah (International Journal of Marine Engineering Innovation and Research, 2025)
Flettner rotor is a technology that utilizes the natural wind to help the oncoming vessel. The working principle of the flettner rotor corresponds to the theory of magnus effect, in which the force arises due to the difference in pressure between the two sides of the flettner rotor. In this research the simulated flettner rotor has a diameter of 3 meters with a height of 18 meters. Simulations were performed 16 times with variations performed on rotation of rotor (0, 100, 300, and 500 rpm) and wind speed (5, 10, 15, and 20 knots). Flettner rotor analysis is done by computational fluid dynamic method. CFD results state that the largest coefficient lift value is on the flettner rotor with rotation 500 rpm with wind speed 20 knots that is equal to 91,13. While in its use of 4000 DWT container vessel, flettner rotor is more work at the speed of vessel 10 knot with rotation speed of flettner rotor 500 rpm and wind speed 5 knot that is equal to 17,438% from force that must be expended to move ship.